ANALISIS POTENSI KEBANGKRUTAN DENGAN MENGGUNAKAN ALTMAN SCORE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013 – 2017 - Zulfikar Zulfikar; Fariyanti Fariyanti; Liana Febrianti (Jurnal Eksis, 2019)
This study aims to determine the potential bankruptcies that occur in mining companies listed on the BEI by using the method of Altman Z”-Score modification. The object of research is a mining sector company listed on Indonesia Stock Exchange, the method used is the method Altman Z-Score Modification (1995) with the equation Z" = 6.56X1 + 3.26X2 + 6.72X3 + 1.05X4. In this study there are four independent variables, such as Working Capital to Total Assets (X1), Retained Earning to Total Assets (X2), Earning Before Interest and Tax to Total Assets (X3), Book Value of Equity to Total Liability (X4). The dependent variable in this study is Z "where Z" = 6.56X1 + 3.26X2 + 6.72X3 + 1.05X4. The results of this study show that three companies during the year 2013 - 2017 showed a decline in financial conditions. PT Perdana Karya Perkasa, Tbk and PT Golden Eagle Energy Tbk for 2013 are on healthy criteria with Score more than 2,6. For 2014 is on the gray area criteria. And in 2015 - 2017 the financial condition of both companies continues to decline and experience the potential for bankruptcy with score below 1,1. While the worst financial condition experienced by PT Atlas Resource from the year 2013 - 2017 is on the criteria of potentially bankruptcy because it has score less than 1,1. It is the performance of these three companies is known to continuously decline over the period of 2013 - 2017Keywords: Altman Z"-Score, Potential Bankruptcy, Mining Company